Obstructive Sleep Apnoea Syndrome and Diabetes. Fortuitous Association or Interaction? - Greco, Carla; Spallone, Vincenza (Current Diabetes Reviews, 2016)
This review explores the relation between obstructive sleep apnoea syndrome (OSAS) and diabetes. It aims to address the following issues: 1. the epidemiological evidence of the association between OSAS and type 2 diabetes; 2. the independence of this association from the comorbidities shared by the two conditions; 3. the chronological and quantitative characteristics of this association (Which comes first? Is there severity interdependence? Is treatment of one condition able to modify the natural history of the other?); 4. the mechanisms that make interaction plausible; 5. the impact of the OSAS-diabetes relation on micro- and macrovascular diabetic complications. OSAS is common in type 2 diabetes. Despite the association being affected by the confounding action of type 2 diabetes comorbidities (also risk factors for OSAS), it does not seem to be fully attributable to them. There is also a relation between OSAS severity and glucose metabolism alteration. A link between OSAS and insulin resistance appears early, prior to impaired glucose tolerance and the onset of diabetes. Therefore, a debate is ongoing on the pathogenetic role of OSAS in type 2 diabetes development and any consequent relevance to diabetes treatment with no conclusive evidence to date. A multiplicity of hypothetical mechanisms may mediate this relation. Most experimental findings support sympathetic activation and changes in chemoreflex sensitivity based on the interaction between chemoreflex and baroreflex. Some studies suggest bidirectional relationship between OSAS and diabetes, additive or synergistic effects for diabetic complications and a reciprocal enhancement in their impact on hypertension and cardiovascular disease. Clarification of these items could benefit diabetes management and prevention of diabetic cardiovascular complications.
Keywords: chemoreflex